Adolescent's motivation and their perceptions of learning contexts of foreign language - Ana Raquel Abelha Cavenaghi; José Aloyseo Bzuneck; Sueli Édi Rufini (Estudos de Psicologia (Campinas))
The aim of the present study was to investigate motivational orientations of 396 adolescents of public schools and their perceptions of their learning contexts. About half of the sample suited English as a compulsory language, while others studied Spanish as an elected language. Data were collected through a Likert-type self report questionnaire with questions related to mastery and work avoidance achievement goals, to perceptions of interesting classes and utility value. Results showed significant positive relations among mastery goal orientation and perceptions of interesting classes and utility, and negative relations among work avoidance goal orientation and those variables. Regression analyses showed that perceptions of interesting classes and utility value predict mastery goal orientation. Some significant differences aroused among students of the two learning contexts. Results were discussed in the light of motivational theories and some suggestions for new researches and for educational practices as well with adolescents were drawn.